“Oh hell no, we don't talk to police”: insights on the lack of cooperation in police investigations of urban gun violence - Brunson, Rod K. (Criminology & public policy, 2019)
We conducted face‐to‐face interviews with 50 young Black men, residents of high‐crime neighborhoods in Brooklyn and the Bronx, individuals who had considerable knowledge about illegal gun markets and the resulting bloodshed. Our findings confirm that distressed milieus reliably fail to produce cooperative witnesses as a result of the cumulative impact of anti‐snitching edicts, fear of retaliation, legal cynicism, and high‐risk victims’ normative views toward self‐help.